2010
DOI: 10.1002/pssr.201004047
|View full text |Cite
|
Sign up to set email alerts
|

Efficient light trapping in a fluorescence solar collector by 3D photonic crystal

Abstract: Fluorescence collectors [1,2] provide efficient concentration and spectral dispersion of solar light for the conversion in multispectral solar cells such as tandem or triple cells [3,4] that allow reduction of cost and increase in efficiency [5][6][7]. One of the principle drawbacks of fluorescence collectors (flucos) consist in the loss of photons through the escape cone resulting from the lack of total reflection due to the contrast in refractive indices of fluco and its environment. This loss can be reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Simulations carried out by Goldschmidt and co-workers 66,67 have shown 20% increases in efficiency with band edge lters. An increase in edge emission with the use of photonic opal crystals was also reported by Knabe et al 68 Debije et al 69,70 observed up to 12% more light collected on the edge of the collector by using Recently researchers have started attempting to improve photon collection efficiency by restricting the molecular orientation of the dye inside the collector. For example, a planar aligned dye with its absorbing axis parallel to the edge of collection will have an increased light output and a respective reduction edge light output in a direction perpendicular to the absorption axis.…”
Section: Advanced Photonic Conceptsmentioning
confidence: 77%
“…Simulations carried out by Goldschmidt and co-workers 66,67 have shown 20% increases in efficiency with band edge lters. An increase in edge emission with the use of photonic opal crystals was also reported by Knabe et al 68 Debije et al 69,70 observed up to 12% more light collected on the edge of the collector by using Recently researchers have started attempting to improve photon collection efficiency by restricting the molecular orientation of the dye inside the collector. For example, a planar aligned dye with its absorbing axis parallel to the edge of collection will have an increased light output and a respective reduction edge light output in a direction perpendicular to the absorption axis.…”
Section: Advanced Photonic Conceptsmentioning
confidence: 77%
“…The first approach is used to enhance the absorption of photons with photon energy below the band gap so that the absorption coefficient for these photons is not so low, the second one to reduce for example the reemission through the escape cone in a fluorescence solar collector [2]. There are different methods to achieve light trapping: From a simple Bragg filter up to 3d photonic crystals which have several stop gaps or even a complete band gap.…”
Section: Introductionmentioning
confidence: 99%
“…Modification and enhancement of the fluorescence in photonic structures is important for development of optical sensors [ 1 ] and improvement of the fluorescence efficiency [ 2 ] and light harvesting ability in solar cells [ 3 ]. Most papers (see, for example, reviews [ 1 , 4 ]) deal with experimental and theoretical aspects of the fluorophores embedded in the multilayered films forming one-dimensional (1D) photonic crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Photonic stop zones in 3D structures have been already proved useful for blocking undesirable light emission [ 9 ]. In particular, this effect was used to avoid leakage of light from the dye-sensitized solar cells [ 3 ], to suppress the radiative channels [ 10 ], and in such a way to improve the Förster resonance energy transfer between the dye molecules situated inside the photonic structure [ 11 ].…”
Section: Introductionmentioning
confidence: 99%